Perancangan Pengalaman Pengguna Aplikasi Pencari Partner Lomba Bagi Mahasiswa Berbasis Mobile Menggunakan Metode Design Thinking - Mochamad Ilham Irwinansyah; Herman Tolle; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Based on a survey on 350 students of Faculty of Computer Science, Universitas Brawijaya, this study found that 80% of respondents had felt confused in finding team members to take part in the competition. To overcome the issue, a user experience to make mobile applications needed to assist students in finding team members. The method used in this study is the design thinking method, which consist of gathering information by conducting interviews and distributing questionnaires to respondents to find out problems and users' behavior, analyzing users' needs to design priorities scale, formulating solutions of main problems, creating prototypes to implement the solutions into visual form, and usability testing to assess aspects of effectiveness, efficiency, and user satisfaction with application design. Usability testing is carried out using two methods, namely task scenarios to measure effectiveness and efficiency and System Usability Scale (SUS) to measure satisfaction. The design of the solution got score of 85% in the terms of effectiveness, 62.87% in the terms of efficiency, and 72.5% in the terms of satisfaction. The design of the solution obtained a final usability value of 73.46% which is included in group B (good).